Amtrak in the heartland - Sanders, Craig (Railroads past and present., 2006)
"Craig Sanders has done an excellent job of research ... his treatment is as comprehensive as anyone could reasonably wish for, and solidly based. In addition, he succeeds in making it all clear as well as any human can. He also manages to inject enough humor and human interest to keep the reader moving." 'Herbert H. Harwood, author of The Lake Shore Electric Railway Story and Invisible Giants: The Empires of Cleveland's Van Sweringen Brothers A complete history of Amtrak operations in the heartland, this volume describes conditions that led to the passage of the Rail Passenger Service Act of 1970, the formation and implementation of Amtrak in 1970'71, and the major factors that have influenced Amtrak operations since its inception. More than 140 photographs and 3 maps bring to life the story as told by Sanders. This book will become indispensable to train enthusiasts through its examination of Americans' long-standing fascination with passenger trains. When it began in 1971, many expected Amtrak to last about three years before going out of existence for lack of business, but the public's continuing support of funding for Amtrak has enabled it and the passenger train to survive despite seemingly insurmountable odds